FACTORS AFFECTING EMPLOYEE PERFORMANCE: CASE STUDY AT PERMATA HATI HOSPITAL RIAU, INDONESIA - Hetty Ismainar; Sandi Iljanto; Efrianti Efrianti (Proceedings of the International Conference on Applied Science and Health, 2017)
Background: Employees are important factors in the organization to achieve the goal. The employee's performance will affect the quality of service. As we know that patient expectations are getting the best service. From the preliminary survey, we discovered some patient complaints; attitudes, communication and undisciplined by employees. Since last 3 years, the hospital quality service indicator has decreased, BOR (Bed Occupancy Rate) <60-80% (Ministries of health Standard). Aims: To determine the factors affect the employees’ performance in Permata Hati Hospital Riau Indonesia Methods: This research used the analytical quantitative study design with cross sectional study. The study was carried out in Mei-June 2014 in Permata Hati Hospital. We used questionnaires for collecting data, The sample of the research are employees in the provision of services to patients directly, totally 154 respondents. Consists of: health workers (nurses, midwives, laboratory, pharmacy, radiology, doctor) and administrative and finance personnel. The dependent variable is employees’performance and the independent variables are: leadership, salary, supervision, and training. Processing data using statistical calculation: univariate, bivariate and multivariate with multiple logistic regression test. Results: There was a significantly strong correlation between independent variables toward the performance of employees (pvalue <0.05). Leadership exerted a significant effect on performance (exp (B) 2.025), salary significant effect on performance (exp (B) 2.029), supervision significant effect on performance exp (B) 1.525) and training significant effect on performance (exp (B) 2.991). Conclusion: Training is the dominant factor affecting the performance of employees in Permata Hati Hospital. It is a necessary to build a roadmap of continuous training in enhancing the competence and quality of service, monitoring and evaluation of performance and performancebased finance system.